2018
DOI: 10.1021/acs.joc.8b00610
|View full text |Cite
|
Sign up to set email alerts
|

Anomer Preferences for Glucuronic and Galacturonic Acid and Derivatives and Influence of Electron-Withdrawing Substituents

Abstract: Equilibrium anomeric ratios are reported for pyranoses (hemiacetals) of glucuronic and galacturonic acid and their derivatives. These are compared to related gluco- and galactopyranoses and to deoxyfluorogluco- and deoxyfluorogalactopyranoses. An association between axial anomer stability and the sum of H NMR downfield chemical shifts for protons H-3 and H-5 was observed in DO with gluco- and galactopyranoses as reference compounds. When compared to 2-hydroxytetrahydropyran in water, introduction of three OAc … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 58 publications
(116 reference statements)
0
20
0
Order By: Relevance
“…A systematic study involving the determination of the anomeric ratios of glucose, galactose and their monodeoxyfluorinated analogues (Table 1) showed that there was no significant variation upon deoxyfluorination. 52 However, in all cases, deoxyfluorination lead to an increased preference for the axial anomer, which was explained by the larger electron withdrawing effect of fluorine compared to that of OH. This results in an increased deshielding of the nearby axial C-H bonds, resulting in a reduced 1,3-diaxial repulsion (or increased intramolecular electrostatic interaction).…”
Section: The Influence On Carbohydrate Structure and Conformationmentioning
confidence: 97%
See 2 more Smart Citations
“…A systematic study involving the determination of the anomeric ratios of glucose, galactose and their monodeoxyfluorinated analogues (Table 1) showed that there was no significant variation upon deoxyfluorination. 52 However, in all cases, deoxyfluorination lead to an increased preference for the axial anomer, which was explained by the larger electron withdrawing effect of fluorine compared to that of OH. This results in an increased deshielding of the nearby axial C-H bonds, resulting in a reduced 1,3-diaxial repulsion (or increased intramolecular electrostatic interaction).…”
Section: The Influence On Carbohydrate Structure and Conformationmentioning
confidence: 97%
“…Fluorinated phosphonate of general structure 6.2 and 6.3 have been also developed either as non-hydrolyzable analogues of glycosyl-1phosphates (6.2) or as transition state analogues (6.3) 142 of GTs or, more generally, enzymes processing carbohydrates phosphorylated at the anomeric position. 64,143 Nucleotide-sugars fluorinated at the 3-, 4-, 5-or 6-position of the sugars have also been synthesized as enzymatic probes, 52,56,144 and have been successfully applied as chain terminator agents of polysaccharide biosynthesis. 145 In molecules 6.1, the electron-withdrawing character of the fluorine atom is believed to destabilize the transition state of the glycosylation reaction, which likely displays a substantial cationic character.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to keep in mind that the modification of carbohydrates with functional groups that are more electron-withdrawing (e.g., OH to F, CO 2 − in uronic acids), regardless of position, has been shown to increase stability of and preference for the α-anomer [88]. Although somewhat counter-intuitive, since electron-withdrawing groups reduce electron density on the endocyclic- O -atom and thereby would reduce the strength of the endo-anomeric effect, it is suggested that these electron-withdrawing substituents can reduce steric gauche interactions and enhance favorable Coulombic interactions between the C-1 and C–H ring substituents [88].…”
Section: Replacement Of Oh Functional Groupsmentioning
confidence: 99%
“…The anomeric effect isoccurred when two electronegative substituents are attached to a sp 3 -hybridized carbon atom. Many theoretical investigations have assessed the anomeric effect [19][20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%